Some applications of Maia's fixed point theorem for Fredholm integral equation systems - FILIP, Alexandru-Darius (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
The aim of this paper is to study the existence and uniqueness of solutions for some Fredholm integral equation systems by applying the vectorial form of Maia’s fixed point theorem. Some abstract Gronwall lemmas and an abstract comparison lemma are also obtained. Mathematics Subject Classification (2010): 47H10, 47H09, 34K05, 34K12, 45D05, 45G10, 54H25. Received 20 October 2019; Revised 28 February 2020; Accepted 08 May 2020.